The Stefan–Boltzmann law: two classical laws give a quantum one. (7th October 2015) - Paul, H; Greenberger, D M; Stenholm, S T; Schleich, W P
Abstract: Due to the universality of blackbody radiation the constant in the Stefan–Boltzmann law connecting the energy density and temperature of blackbody radiation is either a universal constant, or built out of several universal constants. Since the Stefan–Boltzmann law follows from thermodynamics and classical electrodynamics this constant must involve the speed of light and the Boltzmann constant. However, a dimensional analysis points to the existence of an additional universal constant not present in the two classical theories giving birth to the Stefan–Boltzmann law. In the most elementary version this constant has the dimension of an action and is thereby proportional to Planck's constant. We point out this unusual phenomenon of the combination of two classical laws creating a quantum law and speculate about its deeper origin.